Catecholamine effects upon rat hypothalamic corticotropin-releasing hormone secretion in vitro. - Calogero, A E (1988)
To further our understanding of the functional role of catecholaminergic systems in regulating hypothalamic corticotropin-releasing hormone (CRH) secretion, we assessed the direct effects of a multiplicity of catecholamine agonists and antagonists on hypothalamic CRH secretion. To accomplish this, we used an in vitro rat hypothalamic organ culture system in which CRH secretion from single explants was evaluated by a specific RIA (IR-rCRH). Norepinephrine (NE) stimulated IR-rCRH secretion dose dependently, with peak effects in the nanomolar range. The effect of NE was antagonized by the mixed alpha antagonist phentolamine, the alpha 1 antagonist prazosin, and the alpha 2 antagonist yohimbine, but not by the beta blocker, L-propanolol. Compatible with these data were the findings that the alpha 1 agonist phenylephrine and the alpha 2 agonist clonidine both stimulated IR-rCRH secretion in a dose-dependent fashion. On the other hand, whereas the beta agonist, isoproterenol, caused a weak, non-dose-dependent increase in IR-rCRH secretion, this effect could not be antagonized by L-propanolol. Despite pretreatment with serotonin and acetylcholine antagonists, the effect of NE upon IR-rCRH secretion was undiminished, suggesting that NE-induced CRH secretion is not mediated by either neurotransmitter. On the other hand, pretreatment with gamma-aminobutyric acid (GABA) attenuated NE-induced IR-rCRH secretion. Whereas epinephrine (E) stimulated IR-rCRH secretion, this occurred only at higher concentrations, and was antagonized by phentolamine, but not by L-propanolol. Dopamine (DA) had a weak stimulatory effect that could be antagonized by the DA1 receptor antagonist, SCH 23390, but not by phentolamine. We conclude that NE and E stimulate hypothalamic IR-rCRH secretion via alpha 1 and alpha 2 receptors. The effect of NE upon IR-rCRH secretion is not apparently mediated by serotonergic or cholinergic interneurons, but is modulated by the inhibitory neurotransmitter, GABA. These data support the idea that the central catecholaminergic systems are excitatory rather than inhibitory upon CRH secretion when acting directly at the hypothalamic level.